Analysis of the Effect of Work Discipline and Work Experience on Employee Performance Moderated by Organizational Commitment to PT HKI Pekanbaru-Dumai Rest Area Development Project - Hardiansyah Lukita; Mesra B. (International Journal of Management, Economic and Accounting, 2023)
This study was conducted to analyze the effect of work discipline and work experience on employee performance moderated by the organization's commitment to PT HKI Pekanbaru-Dumai Rest Area Development Project. The sample in this study was 80 respondents who were contract employees. The analysis method used is moderating regression analysis. This research was conducted by statistical methods processed with the help of SPSS v. 25 Software. The results showed that partially the variables of Work Discipline and work experience had a significant positive effect on Employee Performance. The results of the moderation test explain the commitment of decent work to be a moderation variable and strengthen the relationship of work discipline variables to employee performance. While work commitment is not worthy to be a moderation variable and weakens the relationship of work experience variables to employee performance.